2005
DOI: 10.1590/s0085-56262005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Density and distribution of nests of Mycetophylax simplex (Emery) (Hymenoptera, Formicidae) in areas with mobile dunes on the northern coast of Rio Grande do Sul, Brazil

Abstract: ABSTRACT. Density and distribution of nests of Mycetophylax simplex (Emery) (Hymenoptera, Formicidae) in areas with mobile dunes on the northern coast of Rio Grande do Sul, Brazil. Studies on lower attines are scarce, especially on nesting and foraging ecology and behavior. This study aimed to contribute to the knowledge of an Attini in dunes ecosystems through the description of density and spatial distribution of Mycetophylax simplex (Emery, 1887) nests in a strip of mobile dunes in the Praia Grande beach, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Our study confirms the few previous biogeographic records on basal Attini inhabiting coastal environments (Kempf, 1964;Diehl-Fleig et al, 2003;Albuquerque et al, 2005). For the first time information on preferred microhabitats at sandy beach sites is provided.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms the few previous biogeographic records on basal Attini inhabiting coastal environments (Kempf, 1964;Diehl-Fleig et al, 2003;Albuquerque et al, 2005). For the first time information on preferred microhabitats at sandy beach sites is provided.…”
Section: Discussionsupporting
confidence: 91%
“…Their symbiotic fungi are closely related to some free-living forms . Various nesting habitats were described (Green et al, 2002;Solomon et al, 2004), amongst them sandy beaches (Albuquerque et al, 2005). For a project on taxonomy of basal Attini in Brazil, we collected ants of the species Mycetophylax conformis, M. simplex and Cyphomyrmex morschi at such sites in southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Albuquerque et al (2005) studying the patterns of distribution of this species in Restinga found that the spatial arrangement of their nests was primarily determined by physical characteristics of the environment, because this species was never found in habitats other than Restinga open dunes. These authors explain that the occurrence of this ant species is possibly determined by the conditions and availability of resources rather than by competition.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling sites (Fig 1) Diehl-Fleig, 1994;Diehl-Fleig & Fleig, 1997;Haubert et al, 1998;Flores et al, 2002;Diehl et al 2006;Florencio & Diehl, 2006;Marchioretto & Diehl 2006 (Diehl-Fleig et al, 2000;Hameister et al, 2003;Albuquerque et al 2005;Diehl, unpub. ms.); 4) grasslands in the Caçapava do Sul (30° 47' S, 52° 24' W; 220 m a.s.l.)…”
Section: Geomorphological Units Of Rio Grande Do Sulunclassified